Overexpression of DBF-Interactor Protein 6 Containing an R3H Domain Enhances Drought Tolerance in Populus L. (Populus tomentosa) - Liu, Yang; Yao, Xinzhuan; Zhang, Lu; Lu, Litang; Liu, Renxiang (Frontiers in Plant Science, 2021)
Drought is the first disaster that endangers the production of agriculture and animal husbandry, which affects the distribution, growth, yield and quality formation of crops. DIP1, as a potential regulator of DBF1 activity, only played an important role in response to drought stress in maize. In this study, we identified six DIP genes in tobacco and selected NtDIP6 as a candidate gene for genetic modification verification based on phylogenetic tree and structure analysis. We generated over-expressing NtDIP6 gene transgenic tobaccos and poplars with no obvious change in phenotype between WT and transgenic plants by Agrobacterium-mediated method. Our results of drought experiment showed that over-expressing NtDIP6 gene transgenic tobaccos and poplars displayed greater drought stress tolerance in comparison with WT. The content of antioxidant defense enzymes (POD and CAT) and the photosynthesis rate were increased in NtDIP6-Ox transgenic poplar, and the content of MDA was decreased in NtDIP6-Ox transgenic poplars, suggesting that over-expression of NtDIP6 enhance the antioxidant capacity of transgenic poplar. Furthermore, the result of RT-qPCR showed that the expression level of drought-related response genes was significantly increased in NtDIP6-Ox transgenic plants. These results indicated that the NtDIP6, as a positive response regulator, improved drought stress tolerance by scavenging superoxide through the accumulation of antioxidant defense enzymes.